FAKTOR-FAKTOR YANG MEMENGARUHI IMPLEMENTASI PROGRAM DETEKSI DINI KANKER SERVIKS MELALUI PEMERIKSAAN IVA DI PUSKESMAS PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Susan Helena Ginting; Achmad Rifai; Ika Nur Saputri (NHM PRESS, 2023)
Cervical cancer were the second ranks for the type of cancer that caused the highest death for women in the world. The incidence of cervical cancer greatly affects the quality and productivity of life of sufferers and their families, also greatly affects the government's health financing sector. This study aimed to analyze the factors that influence the implementation of cervical cancer early detection programs through IVA examination. This study used a qualitative method with a descriptive design. The main informants in this study were 5 midwives who served in the cervical cancer early detection program through IVA examinations. The triangulation informants consisted of the head of the health center, program managers from the district health office, cadres and patients who had already had an IVA examination. This study found that the implementing officers of the IVA program had not been optimal in program socialization, so that program socialization had not reached the community and affected program achievement targets. Implementation of cervical cancer early detection program through IVA examination has not run optimally. Community Health Centers was expected to increase cross-program and cross-sectoral collaboration and integrate with routine activities in the community, for example: associations, wirit, social gathering, and other traditional events. The involvement of cadres must be accompanied by assistance and supervision of implementing officers from the puskesmas.